El entorno social-familiar en la vulneración de los derechos de los niños con discapacidad - Atencio-González, Rously Eedyah; Fernández-Aguilar, Angélica Narcisa; Fernández-Aguilar, Daniel Eduardo; Yong-Zambrano, Rudy Gabriela (IUSTITIA SOCIALIS, 2021)
El entorno social-familiar en la vulneración de los derechos de los niños con discapacidad